Effects of strength, explosive and plyometric training protocol on energy cost of running in high-level ultra-marathoners - Giovanelli, N.; Taboga, P.; Lazzer, S. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Effects of strength, explosive and plyometric (SEP) training on endurance performance have been studied in different sport situations but there is a lack of information related to the effects of SEP training on ultra-marathoners. Thus, the aim of this study was to evaluate the effects of a 12-week SEP training protocol on the cost of running (Cr) in high-level ultra-marathoners and to define the causes of an eventual change in Cr. Methods: Twenty-five male runners (38.2±7.1 years; BMI: 23.0±1.1 kg·m-2; V O2max: 55.4±4.0 mlO2/kg/min) were divided into an exercise (EG=13) and control group (CG=12). Before and after a 12-week SEP training protocol, Cr and springmass model parameters at 8, 10, 12, 14 km/h were calculated. Maximal muscle power of the lower limbs (MMP), morphological properties of the gastrocnemius medialis (GM) and triceps surae tendon stiffness (ktendon) were measured. Results: In EG, Cr decreased significantly (p<0.05) at all tested running speeds by mean -4.2±1.5%, contact time (tc) increased at 8, 10 and 12 km..h-1 by mean 4.4±0.1% and aerial time decreased by -25.6% at 8 km/h (p<0.05). Further, inverse relationships between changes in Cr and MMP at 10 (p=0.013; r=-0.67) and 12 km/h (p<0.001; r=-0.86) were shown. Conversely, no differences were detected in the morphological properties of the GM and ktendon. In CG no differences were shown in any of the studied parameters. Discussion: 12-week SEP training program lower the Cr in high-level ultra-marathoners at submaximal speeds. For these athletes the small improvement in Cr (~4%) can lead to an important step forward in the rankings. In the present study stride length and stride frequency did not change after the training protocol, but tc increased, as shown by Ferrauti et al.(2010). According to the cost of generating force hypothesis (Kram and Taylor 1990), running with longer tc should be more economical, since it requires slower and less expensive fibers and the force is applied in a longer period of time. In agreement with this hypothesis the increased tc could in part explain the lower Cr. Further, an inverse relationship between changes in MMP and changes in Cr at 10 and 12 km/h suggests that athletes who slightly improved their MMP also decreased their Cr at submaximal speeds suggesting that MMP is an important parameter in determining Cr, as previously shown (Lazzer et al. 2015). In conclusion, we suggest to add at least three sessions per week of SEP exercises in the normal endurance-training program.